Incorporating the Value of Religious Moderation in Islamic Education Learning - Huda, Mualimul (Al-Hayat: Journal of Islamic Education, 2024)
This article aims to analyze strategies, methods and models for internalizing the values of religious moderation through the role of teachers and learning Islamic education through curriculum and learning, as well as their implications for forming student character. This research uses a qualitative approach. Data collection techniques use semi-structured interviews, supporting documentation and observations of a series of learning processes in and outside the classroom. Checking the validity of the data uses triangulation techniques. Data analysis was carried out using the stages of data collection, data reduction, data presentation, and concluding/verification. This research shows that internalising religious moderation values includes planning, implementation, organizing and evaluation. Several methods of internalizing the importance of religious moderation include exemplary methods, motivation, habituation, insertion methods, enforcing rules and choosing teaching methods. In general, internalization can be grouped through the learning culture approach in the classroom and school culture. The stages include transforming values, building communication and interaction between teachers and students and synergizing mental attitudes and personalities. The model for integrating the importance of religious moderation through the Islamic education curriculum and learning can be carried out using informative insertion, confirmative insertion and corrective insertion methods. The implications of internalizing the values of religious moderation positively impact increasing student discipline, tolerance, compliance with school rules, respect, and social awareness.